2013
DOI: 10.1111/1467-9566.12040
|View full text |Cite
|
Sign up to set email alerts
|

Fatalism and short‐termism as cultural barriers to cardiac rehabilitation among underprivileged men

Abstract: Cardiovascular diseases are a leading cause of death and disability in Canada, and individuals of low socioeconomic status appear particularly vulnerable to such disorders. Although many health-related institutions have promoted cardiovascular health and have created cardiac rehabilitation programmes, they have not attained their desired outcomes, especially amongst socioeconomically deprived men. Drawing on Pierre Bourdieu's sociocultural theory, this qualitative study aims to understand the social mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
(71 reference statements)
1
37
0
Order By: Relevance
“…For instance, socioeconomically disadvantaged groups often experience a perpetual sense of urgency to respond to immediate needs such as food, shelter and employment (Miller and Brown, 2005;Hankivsky, 2007). They are characterized by a strong present-time orientation (short-termism) and weaker preventative attitudes; living close to economic necessity reduces the ability to invest in future health whereas more affluent socioeconomic groups have greater latitude in this regard (Boltanski, 1971;Dumas and Bournival, 2011;Savage et al, 2013). Indeed, social epidemiologists have presented a growing and convincing body of data linking social and material deprivation with ill-health at the population level, thus bringing attention to upstream social determinants of health (that is, income level, housing quality, job security, early life circumstances) over an exclusive focus on individual (biological) characteristics and lifestyles (Raphael, 2009;Braveman et al, 2011).…”
Section: Women Lifestyle and Obesity A Critical Approachmentioning
confidence: 99%
“…For instance, socioeconomically disadvantaged groups often experience a perpetual sense of urgency to respond to immediate needs such as food, shelter and employment (Miller and Brown, 2005;Hankivsky, 2007). They are characterized by a strong present-time orientation (short-termism) and weaker preventative attitudes; living close to economic necessity reduces the ability to invest in future health whereas more affluent socioeconomic groups have greater latitude in this regard (Boltanski, 1971;Dumas and Bournival, 2011;Savage et al, 2013). Indeed, social epidemiologists have presented a growing and convincing body of data linking social and material deprivation with ill-health at the population level, thus bringing attention to upstream social determinants of health (that is, income level, housing quality, job security, early life circumstances) over an exclusive focus on individual (biological) characteristics and lifestyles (Raphael, 2009;Braveman et al, 2011).…”
Section: Women Lifestyle and Obesity A Critical Approachmentioning
confidence: 99%
“…[14]). Control beliefs can be defined as a person’s belief that he or she is able to actually perform a (desired) action or behaviour (self-efficacy) and the belief that his or her actions matter for outcomes and events (mastery) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some have labelled low control beliefs as powerlessness or “socialised fatalism” [6]. The latter emphasises the embedding in the socioeconomic environment [4, 7]. Low income hampers the number of available options; control over what to purchase is thus restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Lowest adherence to cardiovascular medications is highest among marginalized groups. 13,14 In a Canadian study looking at cultural barriers to participation in cardiac rehabilitation programs, Savage and colleagues 15 identified that although there is universal health care, there is a 5.4-year difference in life expectancy of men of lower socioeconomic status compared with men of highest socioeconomic status, with an 8.4-year difference in women in the same comparison groups. The investigators concluded that participation in cardiac rehabilitation and making healthy lifestyle choices are socially sensitive matters.…”
Section: Underserved Populationsmentioning
confidence: 99%
“…The investigators concluded that participation in cardiac rehabilitation and making healthy lifestyle choices are socially sensitive matters. 15 Because socioeconomic status is such a key determinant of health status, it must be addressed in the context of improving cardiovascular health. There are many barriers to deal with in an underserved population that make it challenging to achieve the previously identified cardiovascular metrics.…”
Section: Underserved Populationsmentioning
confidence: 99%